Anti-NMDA Receptor Autoantibody Is an Independent Predictor of Hospital Mortality but Not Brain Dysfunction in Septic Patients - Malfussi, Hamilton; Santana, Iara Vidigal; Gasparotto, Juciano; Righy, Cassia; Tomasi, Cristiane Damiani; Gelain, Daniel Pens; Bozza, Fernando A.; Walz, Roger; Dal-Pizzol, Felipe; Ritter, Cristiane (Frontiers in Neurology, 2019)
The presence of autoantibodies against neuronal cell surface or synaptic proteins and their relationship to autoimmune encephalitis have recently been characterized. These autoantibodies have been also reported in other pathologic conditions; however, their role during sepsis is not known. This study detected the presence of autoantibodies against neuronal cell surface or synaptic proteins in the serum of septic patients and determined their relationship to the occurrence of brain dysfunction and mortality. This prospective, observational cohort study was performed in four Brazilian intensive care units (ICUs). Sixty patients with community-acquired severe sepsis or septic shock admitted to the ICU were included. Blood samples were collected from patients within 24 h of ICU admission. Antibodies to six neuronal proteins were assessed, including glutamate receptors (types NMDA, AMPA1, and AMPA2); voltage-gated potassium channel complex (VGKC) proteins, leucine-rich glioma-inactivated protein 1 (LGI1), and contactin-associated protein-2 (Caspr2), as well as the GABAB1 receptor. There was no independent association between any of the measured autoantibodies and the occurrence of brain dysfunction (delirium or coma). However, there was an independent and significant relationship between anti-NMDAR fluorescence intensity and hospital mortality. In conclusion, anti-NMDAR was independently associated with hospital mortality but none of the measured antibodies were associated with brain dysfunction in septic patients.